A review of Bittacidae (Mecoptera) in Guizhou, China with descriptions of three new species - He, Le-Le; Hua, Bao-Zhen (European Journal of Taxonomy, 2022)
The Bittacidae fauna in Guizhou Province, China is reviewed. Eleven species in the genera Terrobittacus Tan & Hua, 2009 and Bittacus Latreille, 1805 of Bittacidae are documented in Guizhou, including three new species: Bittacus dilobus sp. nov. and Bittacus leigongshanicus sp. nov. from Leigongshan, and Bittacus multisetus sp. nov. from Yushe. A key to species of Bittacidae in Guizhou is provided.